2018
DOI: 10.1590/0103-6440201802120
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Local Application of Alendronate and Parathyroid Hormone on Craniofacial Bone Repair - a Preliminary Study

Abstract: This study aimed to evaluate the effect of two methods of local application of alendronate and parathyroid hormone (PTH) on bone repair and the systemic implications. A critically sized defect (5 mm) was created in the cranial region of twenty-five male Wistar rats, and the bone removed was particulated, and grafted back to the defect with different treatments. The animals were randomly divided into five groups: A1-bone graft immersion in alendronate solution (3 mg/kg) for 5 minutes; P1-bone graft immersion in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
0
4
0
2
Order By: Relevance
“…A previous study observed that a dose of 3 mg/kg caused systemic alterations in animals, with hepatic impairment (28). In Deliberador et al (15) work, local applications of 1 mg/kg alendronate in rat calvaria defects were delivered, the authors concluded that the kidneys showed normal glomeruli, with capillaries surrounding these structures. No impact on the kidneys was observed in any group of their work.…”
Section: -Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A previous study observed that a dose of 3 mg/kg caused systemic alterations in animals, with hepatic impairment (28). In Deliberador et al (15) work, local applications of 1 mg/kg alendronate in rat calvaria defects were delivered, the authors concluded that the kidneys showed normal glomeruli, with capillaries surrounding these structures. No impact on the kidneys was observed in any group of their work.…”
Section: -Discussionmentioning
confidence: 97%
“…It is this phase that would bene t from the use of substances such as ALN, which have the potential to stimulate osteogenic action, reduce bone resorption activity, and assist in the consolidation process (1,(11)(12)(13). When combined with anabolic-active drugs, ALN signi cantly improves bone mineral density and reduces bone fracture (3,8,14,15). Previous research has shown that short-term ALN treatment also improves bone repair around implants installed in the tibias of osteoporotic rats, demonstrating the drug's potential therapeutic effect (16,17).…”
Section: -Backgroundmentioning
confidence: 99%
“…In our study, we have tried to evaluate the response of enzyme activity of serum MMP-9 and TIMP-1 on appropriate treatment in postmenopausal osteoporosis, which must include pharmacological and nonpharmacological therapy. Taking into account the role of bisphosphonates in regulating activation pathways for MMPs in general and in osteoporosis [27,28], as well as the necessity of proscribing adequate exercise program, we were interested in the role of supervised exercise program in this regulation, specifically. We proposed that pharmacological and nonpharmacological "agents," working together, would have the ability to modulate MMPs activity in a period of 3 months.…”
Section: Discussionmentioning
confidence: 99%
“…Como desvantagens, os ALN possuem baixa biodisponibilidade e apresentam efeitos colaterais quando administrados sistemicamente, seja por via oral ou intravenosa, como irritação gástrica e osteonecrose dos maxilares 3 . Portanto, o uso tópico de ALN torna-se uma opção atrativa, pois busca atingir altas concentrações locais do fármaco, eliminando ou minimizando os efeitos adversos indesejados 4 .…”
Section: Introductionunclassified